Experimental study into the dependence of ice-induced vibrations on dynamic structural properties - Ebben, Nick (author) (2021)
Arctic and sub-arctic regions are more and more used to build offshore wind farms. There is a lack of model-scale tests where dynamic sturcutral properties were systematically varied to derive the influence of these properties on boundaries of the three crushing regimes. Those regimes are intermittent crushing, where both the ice load and displacement signal have a sawtooth pattern, frequency lock-in, with its characteristic sinusoidal displacement signal and continuous brittle crushing with smaller random ice loads and structural displacements compared to the two previously mentioned regimes. The first goal of this thesis is to test if an error in the dynamic structural properties (mass, stiffness and damping) has an effect on the transition velocities of the crushing regimes. Secondly, a parameter study has been done to derive trends in the transition velocities when changing dynamic structural properties. Ultimately, in literature proposed dimensionless numbers, which are particularly only taking linear elastic ice parameters into account, have been checked for rightness. To be able to achieve the above mentioned goals of the thesis, a model-scale test campaign has been performed at the Aalto Ice Tank as part of the SHIVER test campagin. 36 unique single degree of freedom configurations have been tested to derive trends in ice-structure interaction when changing dynamic structural parameters. The most notable element of this test campaign was the usage of a real-time hybrid test setup, which allowed the testing of multiple sets of structural parameters while only one physical structure was used. Those test signify that there is a relation between mass, stiffness, natural frequency and damping and transition velocities inbetween the three crushing regimes. When mass, stiffness and natural frequency increase, the boundaries of those regimes shift to lower velocities. An increase in damping caused the velocity of the boundary between frequency lock-in and continuous brittle crushing to go up, while the boundary ...